Power Crisis and Solution in Bangladesh - Haque, Mohammad Asadul; Rahman, Jalalur (Bangladesh Journal of Scientific and Industrial Research, 2010)
Crisis of power is one of the major problems in Bangladesh. Day by day the gap between demand and production is increasing. Moreover, most of the power plants are gas based which will be phased out in future. Misuse, system loss and corruption in power sector are the main issue regarding this crisis. It is possible to control load demand by using compact fluorescent lamp (CFL), transformation of holiday, proper load management, encouraging Independent Power Producers (IPP) and reducing transmission loss. Priority should be given to control misuse and corruption in power sector than generation of power. Proper utilization of renewable energy is the up most choice for solving the power crisis in Bangladesh because it requires low cost and less risk. Initiative should be taken to develop skilled manpower required for the power sector considering renewable energy sources. By incorporating IPP and local Government (GOV), central GOV may take the responsibility to increase the power generation and ensure its proper use in Bangladesh. Key words: Power crisis; Compact fluorescent lamp; Load management; Renewable energy. DOI: 10.3329/bjsir.v45i2.5714 Bangladesh J. Sci. Ind. Res. 45(2), 155-162, 2010